Оптимизация цифрового фильтра для оценивания фокусировки изображений в цифровой оптической микроскопии - Borovitsky, V. N. (PE "Politekhperiodika", Book and Journal Publishers, 2005)
A method is proposed for optimizing a high spatial frequency digital filter used to evaluate image focusing in digital optical microscopy. This method takes into account the dimensional characteristics of the observed object, as well as the parameters and characteristics of the optical system, digital camera, and digital filter. It enables the calculation of the optimal window size of the digital filter, ensuring the maximum signal-to-noise ratio for the focusing metric.